Optical micro-scale mapping of dynamic biomechanical tissue properties - Liang, Xing (2008)
Mechanical forces such as adhesion, shear stress and compression play crucial roles in tissue growth, patterning and development. To understand the role of these mechanical stimuli, it is of great importance to measure biomechanical properties of developing, engineered, and natural tissues. To enable these measurements on the micro-scale, a novel, dynamic, non-invasive, high-speed optical coherence elastography (OCE) system has been developed utilizing spectral-domain optical coherence tomography (OCT) and a mechanical wave driver. Experimental results of OCE on silicone phantoms are in good agreement with those obtained from a standardized indentation method. Using phase-resolved imaging, we demonstrate OCE can map dynamic elastic moduli of normal and neoplastic ex vivo human breast tissue with a sensitivity of 0.08%. Spatial micro-scale mapping of elastic moduli of tissue offers the potential for basic science and clinical investigations into the role biomechanics play in health and disease.